2017
DOI: 10.1111/asj.12848
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among muscle fiber type composition, fiber diameter and MRF gene expression in different skeletal muscles of naturally grazing Wuzhumuqin sheep during postnatal development

Abstract: The aim of this study was to determine the relationships among muscle fiber‐type composition, fiber diameter, and myogenic regulatory factor (MRF) gene expression in different skeletal muscles during development in naturally grazing Wuzhumuqin sheep. Three major muscles (i.e. the Longissimus dorsi (LD), Biceps femoris (BF) and Triceps brachii (TB)) were obtained from 20 Wuzhumuqin sheep and 20 castrated rams at each of the following ages: 1, 3, 6, 9, 12 and 18 months. Muscle fiber‐type composition and fiber di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…The authors argued that this factor is more involved in the control of muscle mass than in fiber-type transitions (51). Accordingly, Siqin et al recently explored the relationships among muscle fiber-type composition, diameter, and MRFs expression in different skeletal muscles, they also suggested that MRFs expression patterns were relatively stable with the changes in fiber-type composition and increases in fiber size resulting from mutually interacting processes during muscle development (52). Furthermore, Deldicque et al (53) identified a major signaling cascade by which Cr promotes the differentiation program of C 2 C 12 cells, via p38 MAPK and ERK1/2 pathway, which may increase the expression of transcription factors (i.e., myod and mef2 ) capable of regulating the activation and differentiation of satellite cells.…”
Section: Discussionmentioning
confidence: 99%
“…The authors argued that this factor is more involved in the control of muscle mass than in fiber-type transitions (51). Accordingly, Siqin et al recently explored the relationships among muscle fiber-type composition, diameter, and MRFs expression in different skeletal muscles, they also suggested that MRFs expression patterns were relatively stable with the changes in fiber-type composition and increases in fiber size resulting from mutually interacting processes during muscle development (52). Furthermore, Deldicque et al (53) identified a major signaling cascade by which Cr promotes the differentiation program of C 2 C 12 cells, via p38 MAPK and ERK1/2 pathway, which may increase the expression of transcription factors (i.e., myod and mef2 ) capable of regulating the activation and differentiation of satellite cells.…”
Section: Discussionmentioning
confidence: 99%
“…After dehydration in a series of ethanol gradient solutions (70%, 80%, 90%, and then 95% anhydrous alcohol for 2 min at each solution) and inducing transparency with xylene, samples were embedded in paraffin and were sectioned in serial transverse sections (5 µm thick). Dewaxed serial sections were stained with the traditional hematoxylin and eosin (HE) method to show the histological characteristics of the muscle fibers [17]. The morphological characteristics of the muscle fibers (e.g., diameter, perimeter, area, and density) were measured using CaseViewer 2.2 (3DHISTECH Ltd., Budapest, Hungary) under an electron microscope (Axio IMAGE Z2, Leica microsystems Ltd., Wetzlar, Germany).…”
Section: Muscle Fiber Characteristicsmentioning
confidence: 99%
“…It gradually differentiates from mesoderm-derived cells into myoblasts, merges into myotubes, and matures to form muscle fibers [ 11 ]. At present, skeletal muscle morphology has been widely measured in pig [ 12 , 13 ], chicken [ 14 ] and sheep [ 15 ], while it is rarely studied in rabbit. The researches on rabbit skeletal muscle structure were mainly related to jaw muscle.…”
Section: Discussionmentioning
confidence: 99%